2015
DOI: 10.1097/aco.0000000000000191
|View full text |Cite
|
Sign up to set email alerts
|

Patient-controlled intravenous analgesia remifentanil for labor analgesia

Abstract: Remifentanil PCIA is a valuable analgesic strategy whenever regional analgesia is contraindicated. Using it as first line strategy seems to be contraindicated because of significant respiratory side-effects to the mother. Whenever used advanced and continuous monitoring using capnography, saturation monitoring and one-to-one midwifery care are mandatory!

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Five other systematic reviews with or without meta‐analysis dealing with remifentanil for labour analgesia have been published up to March 2016 . In summary, the previous reviews revealed similar effects of interventions (direction of estimated effects).…”
Section: Discussionmentioning
confidence: 83%
“…Five other systematic reviews with or without meta‐analysis dealing with remifentanil for labour analgesia have been published up to March 2016 . In summary, the previous reviews revealed similar effects of interventions (direction of estimated effects).…”
Section: Discussionmentioning
confidence: 83%
“…As the author mentions, instant intervention to ensure ventilation is needed in such cases, and, similarly, in cases of hypoventilation caused by remifentanil. The major difference is that in the case of remifentanil, hypoventilation usually subsides after several dozen seconds, whereas complications of regional analgesia -respiratory depression and circulatory disorders -generally last slightly longer [10]. Such situations are not even mentioned by the author.…”
Section: In Reply To the Commentary To Commentary To "Remifentanil Fomentioning
confidence: 86%
“…23 24 As a consequence, several editorials and review articles have been published to raise awareness of this risk of maternal respiratory depression and to challenge the validity of Remifentanil PCIA for labor analgesia. [25][26][27][28] By contrast, several cohort studies aimed to be reassuring. In a 2019 retrospective analysis, Melber AA et al reported the results of a 6 years audit (2010-2015) of the outcome data of the RemiPCA SAFE network.…”
Section: Discussionmentioning
confidence: 99%